2000
DOI: 10.1107/s0108768100003633
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transitions of HfV2 at low temperatures

Abstract: We report a high-resolution synchrotron X-ray powder diffraction study on HfV(2), hafnium divanadium, at low temperatures. In this work we show, for the first time, a complete sequence of structural phase transitions of HfV(2) from cubic (Fd3m) to tetragonal (I4(1)/amd) to orthorhombic (Imma) in succession as temperature decreases. Peak splitting and extra diffraction peaks owing to lattice distortion can be clearly distinguished for the low-symmetry phases. The atomic positions and lattice parameters were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 8 publications
6
13
1
Order By: Relevance
“…Well-known examples are HfV 2 [128][129][130][131][132][133] and ZrV 2 [134,135] which show a transformation from the C15 Laves phase structure to a tetragonal or orthorhombic (HfV 2 ) or a rhombohedral (ZrV 2 ) structure at about 110 to 115 K. Detailed investigations of the structural phase transformation in HfV 2 revealed that there is a complete sequence of transformations during cooling from the C15 Laves phase structure to a body-centered tetragonal structure at 112 K and to an orthorhombic structure at 102 K [133].…”
Section: Transformations Into Other Crystal Structuresmentioning
confidence: 99%
“…Well-known examples are HfV 2 [128][129][130][131][132][133] and ZrV 2 [134,135] which show a transformation from the C15 Laves phase structure to a tetragonal or orthorhombic (HfV 2 ) or a rhombohedral (ZrV 2 ) structure at about 110 to 115 K. Detailed investigations of the structural phase transformation in HfV 2 revealed that there is a complete sequence of transformations during cooling from the C15 Laves phase structure to a body-centered tetragonal structure at 112 K and to an orthorhombic structure at 102 K [133].…”
Section: Transformations Into Other Crystal Structuresmentioning
confidence: 99%
“…Superstructure formation in such systems may be driven by electronic and geometrical factors as well as magnetic ordering or magnetostriction. Many examples have meanwhile been reported …”
Section: Introductionmentioning
confidence: 99%
“…In comparison, several theoretical studies also predict cubic HfV2 to be energetically unstable in the ground state, reporting energies of formation between 20 and 35 meV per atom [29,74,75]. Furthermore, experiments show a transformation of cubic HfV2 upon cooling into an orthorhombic structure at around −160 °C [76,77] possibly due to kinetically limited decomposition into elemental V and Hf, since orthorhombic HfV2 also exhibits positive energy of formation [29,75]. However, for sputtered HfV2 at 500 °C (see Figure 2), the change in shape of the main peak at around 38° suggests the first formation of nanocrystals, and the emerging hump around 20° points towards intermetallic HfV2 nanocrystals, since their presence cannot be explained by hcp Hf or bcc V.…”
Section: Phase Formation Of Hfvmentioning
confidence: 94%
“…For ZrV 2 , due to the considerably higher energy of formation in the ground state [71], its energetic stabilization is expected at higher temperatures, potentially explaining the discussed phase formation differences between Hf-V and Zr-V thin films. For comparison, bulk synthesis of HfV 2 includes heat treatments at temperatures above 1200 • C [34,77,79]. The reduction in synthesis temperature to 700 • C is enabled by surface diffusion of adatoms during sputtering [80].…”
Section: Phase Formation Of Hfvmentioning
confidence: 99%